Feeling the gaze : image and affect in contemporary Argentine and Chilean performance - Bulman, Gail A., 1957- (North Carolina studies in the Romance languages and literatures ;, 2022)
"Feeling the Gaze: Image and Affect in Contemporary Argentine and Chilean Performance is the first book-length study to explore the connection between visuality and affect in Latin American theater performances. Taking Argentine and Chilean performances as models, Bulman shows how twenty-first century live performances manipulate images on stage to build an affective bond and lasting impression on spectators that sharpens the plays' socio-historical and political messaging. Through close readings of eight Southern Cone performances originally staged between 2014 and 2019 - many of which have also been performed internationally - Feeling the Gaze showcases the originality and innovation in Argentine and Chilean theater and contributes to existing scholarship on post-dramatic theater, performance studies, visual studies, cultural studies, affect studies, and world theater. By closely examining props, bodies, costumes, lighting, digital images and embedded screens through theoretical lenses, the book illustrates ways in which the artists' manipulation of visual elements on stage captivates spectators emotionally and intellectually"--